Diagnóstico socioambiental participativo da ilha do Atalaia (Salinópolis - PA): vislumbre litorâneo amazônico, um prisma - Costa, Laisa Tocantins Murta (2018)
The Amazonian coastal zone is an extremely fascinating environment in its ecological dimension, enjoying a splendorous biological diversity at the same internationally coveted, as well as in its strategies and ways in which society interferes with the environment. The presence of the islands is a very characteristic feature in this region, represented by a great nominal value added to the “Amazonian caboclo”, a fact that can be easily observed in its mythological culture, strongly linked to the waters. The island of Atalaia, placed in the municipality of Salinópolis has undergone, for decades, heavy anthropic pressure due to irregular occupations and immoderate tourist exploitation, triggering serious concerns in the environmental context for the public authorities, as well as for civil society. The present work aims the recognition of the main socio- environmental problems in the Island of Atalaia (Salinópolis-PA), its connections and ressonances through the conception of a profile and a participatory socio-environmental diagnosis, guided by methodologies applied in Participatory Rural Diagnostics (PRD), such as: the appliance of semi-structured interviews with different social actors operating in the area, the use of questionnaires with different social groups and participatory mapping through social cartography with the local community. The “prism” refers to the combination of historical, environmental, socioeconomic and mythical religious dimensions, which will be explained in a fragmented way despite their irrefutable correlations. The conclusion of the diagnosis, the collective construction of the most urgent demands for the community spurs the critical view of those involved and fostered reflection and inquiries about their actions and defaults towards nature. The public opinion of the social actors implicated regarding the exercise of the right to the ecologically balanced environment and other fundamental entitlements in the territory proves that social mobilization initiatives are extremely necessary but scants in the region.